2012
DOI: 10.4103/0970-9185.92429
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of epidural catheter from lumbar to thoracic space in children: Comparison between 18G and 23G catheters

Abstract: Backgrounds and Objectives:Lumbar-to-thoracic advancement of epidural catheter is a safe alternative to direct thoracic placement in children. In this prospective randomized study, success rate of advancement of two different types and gauges of catheter from lumbar-to-thoracic space were studied.Materials and Methods:Forty ASA I and II children (up to 6 years) undergoing thoracic or upper-abdominal surgery were allocated to either Group I (18G catheter) or Group II (23G catheter). After induction of general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The sum of doses of metamizol as a "rescue drug" was similar in the BF and RF group (Me: 1 [0-2] vs. 1 [0-2], Z = -0.593, P = 0.552). There was also no difference between BF vs. RF in terms of the total number of interventions (Me: 6 [3][4][5][6][7][8] vs. 6 [4][5][6][7]; Z = 0.540; P = 0.588).…”
Section: Modification Of Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…The sum of doses of metamizol as a "rescue drug" was similar in the BF and RF group (Me: 1 [0-2] vs. 1 [0-2], Z = -0.593, P = 0.552). There was also no difference between BF vs. RF in terms of the total number of interventions (Me: 6 [3][4][5][6][7][8] vs. 6 [4][5][6][7]; Z = 0.540; P = 0.588).…”
Section: Modification Of Analgesiamentioning
confidence: 99%
“…Analgesic mixtures containing bupivacaine and fen-tanyl or ropivacaine and fentanyl administered through a thoracic epidural catheter (TEC) are effective in relieving pain after thoracic surgery [8][9][10] . However, bupivacaine is much cheaper than ropivacaine 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have also shown migrations of the caudal epidural catheter defeating the very purpose of their placement. [4,5] On the other side of the spectrum, substantial progress has been made in our understanding of this procedure. The catheter tip placement can be confirmed by various modalities such as radiographic imaging, neurostimulation, and application of ultrasonography (US).…”
Section: Introduction Why This Review?mentioning
confidence: 99%